Effect of the Solvent on the Microstructure of Bi2Te3 Obtained Solvothermal Microwave-assisted Synthesis - R.A. Lyubushkin; O.N. Soklakova; M.N. Yapryntsev; A.E. Vasiliev; E.P. Danshina; O.N. Ivanov (Журнал нано- та електронної фізики)
In the present work, nanoparticles and nanowires have been prepared by solvothermal microwave-assisted synthesis using isopropyl alcohol, dimethylformamide (DMF) and 1,4-dioxane respectively as the solvents. The microstructures of the synthesized powders have been characterized and the relationship with the solvent has been investigated.